Corporate Corruption: A Review and an Agenda for Future Research - Castro, Armando; Phillips, Nelson; Ansari, Shaz (Academy of Management Annals, 2020)
Given its extremely negative impact, it is not surprising that there is extensive literature focused on understanding and reducing corruption. However, the existing academic work focuses largely on corruption in government. Yet, corporations play a key role in much of the corruption that occurs in society and are important contexts for corruption themselves; they are also very different from governments and, we argue, deserve focused study and the development of a coherent theory of corporate corruption. In this article, we define corporate corruption and argue that management researchers are uniquely positioned to contribute to the development of a theory of corporate corruption and the development of solutions to prevent it. We then examine the current state of research on this important topic and propose a framework for organizing research on corporate corruption into four perspectives: corporate corruption as rational action, corporate corruption as institutionalized practice, corporate corruption as cultural norm, and corporate corruption as moral failure. We go on to propose a research agenda for management scholars in some traditional areas of management research to take this important but under-researched topic forward, as well as highlight some of the methodological challenges that management researchers face in conducting research in corporate corruption.